Drivers of grape berry sugar accumulation in field conditions at local scale - de Rességuier, Laure; Inchboard, Lauren; Parker, Amber K; Petitjean, Théo; van Leeuwen, Cornelis (OENO one, 2024)
The final sugar concentration in grapes is an important parameter for winegrowers as it determines the alcohol content by volume of the final wine, allowing the timing of harvest to be optimised. In this research, a comprehensive dataset spanning seven years and 18 sites located in Saint-& Eacute;milion, Pomerol and satellite appellations (Bordeaux, France) was used to assess how growth and developmental factors (berry weight and mid-veraison date, respectively) and environmental factors (vine water status, nitrogen status, and mean air temperature) influence the dynamics of sugar accumulation. The results of this study highlight the strong influence of mean temperature on the timing of maximum sugar accumulation, the duration of sugar accumulation and maximum sugar concentration in grape berries. Berry weight and the rate of sugar accumulation also appeared to be significant drivers of final sugar concentration. Fast ripening and increased berry weight were associated with lower sugar concentrations. Sites were clustered according to parameters driving sugar accumulation dynamics and mapped at the scale of the study area, in order to link these findings to terroir expression. In this study, vine nitrogen status did not emerge as a significant explanatory variable in any of the models developed to analyse sugar accumulation dynamics and berry weight. A small but significant effect of vine water status on the precocity of the plateau and on berry weight was found. These results provide a better understanding of the factors that affect the dynamics of sugar accumulation in grape berries, which can help vine growers adapt to climate change. For example, by promoting practices that delay the onset of ripening to shift to a cooler period of ripening through choice of plant material and management practices. Alternatively, this can be done through an increase in berry weight, which lowers grape sugar and therefore wine alcohol concentration, taking care not to excessively alter the skin-pulp ratio to avoid reducing secondary metabolites.